2020
DOI: 10.1016/j.stem.2019.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Axin2+ Cells Drive Epithelial Homeostasis, Regeneration, and Cancer following Oncogenic Transformation

Abstract: Highlights d Endometrial epithelium self-renews throughout life d Axin2 marks long-lived bipotent stem cells residing at the base of glands d Axin2 + cells fuel endometrial epithelial growth and regeneration d Mutant Axin2 + cells lead to endometrial carcinogenesis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
103
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(106 citation statements)
references
References 51 publications
3
103
0
Order By: Relevance
“…Recently, two studies based on cell lineage tracing with tamoxifen-controlled Cre expression have been published ( Jin, 2019 ; Syed et al, 2020 ). The first study used limited labeling and mathematical analysis in Krt19-Cre/ERT2 and FoxA2-Cre/ERT2 mice crossed with reporter mice ( Jin, 2019 ) and concluded that the stem cell population resides in the intersection zone between luminal and glandular epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, two studies based on cell lineage tracing with tamoxifen-controlled Cre expression have been published ( Jin, 2019 ; Syed et al, 2020 ). The first study used limited labeling and mathematical analysis in Krt19-Cre/ERT2 and FoxA2-Cre/ERT2 mice crossed with reporter mice ( Jin, 2019 ) and concluded that the stem cell population resides in the intersection zone between luminal and glandular epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…The first study used limited labeling and mathematical analysis in Krt19-Cre/ERT2 and FoxA2-Cre/ERT2 mice crossed with reporter mice ( Jin, 2019 ) and concluded that the stem cell population resides in the intersection zone between luminal and glandular epithelium. By contrast, the second study reported that Axin2 + glandular cells can act as drivers of epithelial homeostasis and regeneration ( Syed et al, 2020 ). Cell fate tracing was initiated at either diestrus ( Jin, 2019 ) or metestrus ( Syed et al, 2020 ), which complicates comparative interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endometrial carcinoma (EC), which results from aberrant regeneration in terms of excessive growth of endometrial glands [1], accounts for 4.4% of carcinoma cases among women in 2018 [2] with more than 60,000 cases estimated in the United States in 2019 [3]. As for endometrial precancerous lesions including atypical hyperplasia or endometrial intraepithelial neoplasia and well-differentiated cancer, hysterectomy would not be a feasible and effective optimal choice for them and conservative treatment to preserve fertility for young patients is becoming significantly essential.…”
Section: Introductionmentioning
confidence: 99%